2014
DOI: 10.1111/pbaf.12026
|View full text |Cite
|
Sign up to set email alerts
|

The Flypaper and Asymmetric Effects of Intergovernmental Grants to Quebec Municipalities

Abstract: This study uses a panel fixed effect model to analyze the impact of intergovernmental grants on municipal spending in Quebec. The data from the 1,084 municipalities covering the period 2001-2007 are used for this purpose. The study shows that grants have flypaper and asymmetric effects and that the extent of these effects is sensitive to the type of grants and municipal expenditures. Furthermore, it suggests that conditional grants seem to be a more effective tool for changing the composition of the supply of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
1
12
1
2
Order By: Relevance
“…Tujuan utama dari pelaksanaan transfer adalah untuk mengurangi kesenjangan fiskal yang muncul dalam pembangunan antar daerah. Namun, pemberian transfer dihadapkan pada suatu fenomena umum dalam menunjang keberhasilan pembangunan daerah yaitu terjadi peningkatan pengeluaran daerah sejalan dengan meningkatnya dana transfer dari pemerintah, sehingga pemberian transfer tersebut berakibat pada ketidakefektifan dalam pembiayaan pengeluaran daerah dimana respon belanja daerah lebih besar terhadap transfer, maka fenomena tersebut disebut dengan flypaper effects (Hamilton, 1983;Hines dan Thaler, 1995;Melo, 2002 (Vegh dan Vulettin, 2015), China (Liu dan Zhao, 2011), Denmark (Kjaergaard, 2015), Italia (Bracco et al 2015), Jepang (Kakamu et al, 2014), Kanada (Mehiriz dan Marceau, 2014), Slovenia (Pevcin, 2014) dan Swedia (Dahlberg et al, 2008). Bukti empiris tentang flypaper effect juga ditemukan di penelitian lintas negara yang dilakukan oleh Abbott dan Jones (2012) dan Dell'Anno dan Mourou (2012).…”
unclassified
“…Tujuan utama dari pelaksanaan transfer adalah untuk mengurangi kesenjangan fiskal yang muncul dalam pembangunan antar daerah. Namun, pemberian transfer dihadapkan pada suatu fenomena umum dalam menunjang keberhasilan pembangunan daerah yaitu terjadi peningkatan pengeluaran daerah sejalan dengan meningkatnya dana transfer dari pemerintah, sehingga pemberian transfer tersebut berakibat pada ketidakefektifan dalam pembiayaan pengeluaran daerah dimana respon belanja daerah lebih besar terhadap transfer, maka fenomena tersebut disebut dengan flypaper effects (Hamilton, 1983;Hines dan Thaler, 1995;Melo, 2002 (Vegh dan Vulettin, 2015), China (Liu dan Zhao, 2011), Denmark (Kjaergaard, 2015), Italia (Bracco et al 2015), Jepang (Kakamu et al, 2014), Kanada (Mehiriz dan Marceau, 2014), Slovenia (Pevcin, 2014) dan Swedia (Dahlberg et al, 2008). Bukti empiris tentang flypaper effect juga ditemukan di penelitian lintas negara yang dilakukan oleh Abbott dan Jones (2012) dan Dell'Anno dan Mourou (2012).…”
unclassified
“…The influence of the median voter on the outcomes of the decision-making process stems from the fact that each political coalition needs the support of this elector to win elections and to form the governing coalition. Studies using the median voter framework have shown that municipal expenditures are strongly correlated with the variables used as proxies for the median voter needs for municipal services and the capacity to afford their costs such as population size, property value and median household income [ 22 , 23 , 24 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The fiscal illusion explanation is used in two different ways: one emphasizes politicians responding to voter demand; and one focuses on the political apparatus trying to expand the public sector. The first explains the flypaper effect as the response of rational politicians to the preference of voters said to suffer from fiscal illusion (Courant et al, 1979;Dollery and Worthington, 1996;Hines and Thaler, 1995;Mehiriz and Marceau, 2014). The demand for public service is expressed through the median voter in the constituency, and the flypaper effect is seen as a failure of the voters to correctly evaluate the impact of grants on the costs of public services.…”
Section: Differences In Responses To Changes In Local Government Revenuementioning
confidence: 99%
“…Inspired by the flypaper effect, a more recent literature investigates whether the response to changes in grants from a higher-level authority differs depending on whether grants are decreased or increased (Gamkhar and Oates, 1996;Heyndels, 2001;Mehiriz and Marceau, 2014;Stine, 1994;Volden, 2007). According to the asymmetrical response hypothesis, increases in public spending when grants are increased are expected to be larger than cuts in spending when grants are reduced with a similar amount (Gamkhar and Oates, 1996).…”
Section: Differences In Responses To Changes In Local Government Revenuementioning
confidence: 99%
See 1 more Smart Citation